REPRESENTATION OF ECOLOGICAL EXEGESIS IN ISLAMIC WEBSITES: A CRITICAL STUDY OF THE NU ONLINE AND BULETIN DAKWAH KAFFAH ACCOUNTS - Muh Rizaldi; Siti Dea Ananda (Universitas Nahdlatul Ulama Surakarta, 2026)
The interpretation of ecological verses disseminated through media with different ideological bases has an impact on the construction of meanings that tend to be contradictory. In this context, the ideological configuration of each media influences the way ecological verses are interpreted. The NU Online and Buletin Dakwah Kaffah accounts are Islamic media that actively respond to ecological issues with the content of religious text interpretations that appear significantly different. Therefore, this study aims to analyze the representation of ecological interpretations in the two accounts which are strongly suspected of reflecting their idiological preferences in producing religious discourse related to ecology. This research uses a qualitative method with content analysis as a data analysis tool. The findings of this study show that there are differences in orientation between NU Online and Buletin Dakwah Kaffah in articulating the values of ecological awareness based on Quranic verses. The NU Online account in this case displays a moderate and contextual interpretation of ecology by emphasizing the principle of human responsibility in maintaining the balance of nature. In contrast, the Buletin Dakwah Kaffah account constructs ecological issues in a tolitarian-centralistic framework that emphasizes the dimensions of rigid sharia obedience and inserts provocative political narratives against the role of the government (upholding the Islamic caliphate as the only solution to the ecological crisis). This finding shows how digital space has become an important arena in the formation of a dynamic Islamic ecological discourse while showing the contestation of religious ideologies in responding to environmental issues.